AI for Evaluators: Opportunities and Risks - Aaron Wilson Kates; Kurt Wilson (The Evaluation Center at Western Michigan University, 2023)
We are all familiar with how computers and smartphones have transformed work and productivity. We now stand at a new threshold with another technology that is predicted to further transform the way we work: Artificial Intelligence (AI).  In this article, we hope to take a sober and practical look at AI from the perspective of professional evaluators. We examine how we might use it, how it might transform the nature of our tasks, what threats it might pose to our field, and what evaluators might do to protect themselves and our society from potential adverse effects of this emerging technology.